(untitled) (Slovo, 2025)
The novel Oblomov by Ivan Goncharov, published at a time when literature was concerned with the education and formation of the individual, challenges the conventional form of the bildungsroman by focusing on a character who appears to be static and does not develop in accordance with the typical trajectory of a coming-of-age narrative. In order to comprehend the rationale behind the inactivity of the eponymous character, as well as the phenomenon observed in Russian society and generically referred to as “Oblomovism”, we will analyze how the perception of time and space influences the formation of Oblomov’s personality and differentiates him from his active and lively friend Stolz. The antithesis between the two characters represents a fundamental aspect of the novel, underscoring the contrast between two distinct mentalities shaped by opposing perceptions of time and space. Despite its deviations from the conventional structure of a “Bildungsroman”, the novel Oblomov incorporates sufficient elements of the genre to be regarded as an unconventional iteration of this literary type, particularly in its portrayal of the protagonist’s unique relationship with time and space.